Pain management in the right iliac fossa during the Covid-19 pandemic - Daniel Ovidiu Costea; Lucian Serbanescu; Diana Badiu; Valeriu Ardeleanu; Cristian Mihai Branescu; Anca Zgura; Andreea Cristina Costea (Journal of Mind and Medical Sciences)
Abdominal pain in the right iliac fossa in women may be caused by a complicated ovarian cyst, adnexitis, and appendicitis. The paper analyses the characteristics of patients with right iliac fossa pain admitted during the Covid-19 pandemic. A retrospective analysis on 25 cases with abdominal pain in the right iliac fossa admitted to “St. Apostol Andrei” Emergency County Clinical Hospital Constanta, Romania between March 2020 and March 2021 was performed. In 52% of the cases, the symptomatology remitted with antispasmodics, 4 (16%) patients had cystic torsion and right adnexectomy (group A, without adnexa), 6 (24%) patients had ruptured cysts and right cystectomy, and 2 (8%) had immediate cystectomy together with appendectomy due to signs of peritoneal irritation (group B, adnexa retained). The age, the signs and the symptoms, as well as the inpatient diagnosis in group A were lower compared to patients in group B. The ovarian cyst can become a major surgical emergency if twisted or ruptured and it reaches an important vascular source, especially if it is associated with acute appendicitis, which often poses problems of differential diagnosis. The collaboration between gynecologists and surgeons is essential in the optimal therapeutic solution of these cases.